The Association of Feeding Practices and Sociodemographic Factors on Underweight and Wasting in Children in Ethiopia: A Secondary Analysis of Four Health Surveys from 2000 to 2016. (27th August 2021) - Hiruy, Aschalew Fikru; Xiong, Qianqian; Jin, Qiman; Zhao, Jing; Lin, Xuechun; He, Shuiqing; Abebe, Anissa; Zuo, Xuezhi; Ying, Chenjiang
Abstract: Background: Feeding practices highly influence the nutritional status of children between 6 and 23 months of age in developing countries, including Ethiopia. Therefore, this study was conducted to investigate the association of feeding practices and sociodemographic factors on underweight and wasting of children aged 6–23 months in Ethiopia. Methods: Data on 8003 children 6–23 months of age from four Ethiopia demographic and health surveys (EDHS) from 2000 to 2016 were analyzed using complex sample crosstabs for multivariate analysis. The association of feeding practices and sociodemographic factors on underweight and wasting was assessed via multiple logistic regression analyses adjusting the covariates. The outcomes were reported based on the adjusted odds ratios (ORs) with 95% confidence interval (CI). Results: Male children, very small at birth size children, diarrhea and fever, and short stature mother were risk factors for underweight and wasting ( p < 0.05–0.001). Also, minimum dietary diversity, rich and middle-income families, vitamin A in the previous 6 months and antenatal care visits during pregnancy were protective factors for both underweight and wasting ( p < 0.05–0.001). Minimum meal frequency was significantly related to lower odds of wasting ( p < 0.001). Higher age of the child was significantly associated with underweight ( p < 0.05–0.001); however, it was less likely wasted ( p < 0.05–0.01). Conclusion: The present study depicted that among infant young children feeding core indicators except breastfed, all the other indicators did not met the required standard; however, sociodemographic factors on four health surveys from 2000 to 2016 were associated with underweight and wasting in children in Ethiopia. LAY SUMMARY: Over the years the prevalence of underweight in children aged 6–23 months in the country has shown a significant improvement from 40.2% in 2000 to 34.7% in 2005, then further reduced to 28.9% and 20.0% in 2011 and 2016 EDHS, respectively. In the same manner, the prevalence of wasting in children aged 6–23 months in Ethiopia also observed improvement from 18.9% in 2000 to 16.7% in 2005, then further reduced to 15.4% and 13.9% in 2011 and 2016 EDHS, respectively. Male children, very small at birth size children, diarrhea and fever (for the last 2 weeks), and short stature mother were risk factors for underweight and wasting. Minimum dietary diversity, rich and middle-income families, vitamin A in the previous 6 months and antenatal care visits during pregnancy were protective factors for both underweight and wasting. Minimum meal frequency was significantly related to lower odds of wasting. Higher age of the children was significantly associated with underweight; however, less likely wasted.